How do you prove sec2(x) - tan2(x) = 1?

Prove sec^2(x)-tan^2(x)=1

Let us prove the equation

We know the identity

sin2(x)+cos2(x)=1 ——-(i)

Dividing throughout the equation by cos2(x)

We get

sin2(x)/cos2(x) + cos2(x)/cos2(x) = 1/cos2(x)

We know that

sin2(x)/cos2(x)= tan2(x), and cos2(x)/cos2(x) = 1

So the equation (i) after substituting becomes

tan2(x) +1= 1/cos2(x) ——–(ii)

Now we know that 1/cos2(x)= sec2(x)

So on substitution equation (ii) becomes

tan2(x) +1= sec2(x)

On rearranging the terms we get

sec2x− tan2x = 1

Hence Proved

Leave a Comment

Your email address will not be published. Required fields are marked *


Free Class